Synthesis, crystal structures and dye removal properties of a series of metal-organic frameworks based on N-heterocyclic carboxylic acid ligands - Zong, Zi-ao; Fan, Chuan-bin; Zhang, Xia; Meng, Xiang-min; Fan, Jin; Fan, Yu-hua (Microporous and mesoporous materials, 2019)
Six functional metal-organic frameworks build by 4,4'-(1H-1,2,4-triazol-1-yl)methylenebis (benzonic acid) (H2tmlb), namely: [Zn4(tmlb)4(H2O)]n (1), [Ni4(tmlb)4(H2O)]n (2), [Cu(tmlb)]n (3), [Co(tmlb)]n (4), [Pb(tmlb)(H2O)]n (5), {[Zn(tmlb)(H2tmlb)]H2O}n (6), have been successfully synthesized. The X-ray diffraction analysis show that the complexes 1 and 2 exhibited a two interpenetrating (3, 6, 6)-connected framework with a Schläfli symbol of (4·62)2 (42·610·83) topology. The complexes 3 and 4 show a two interpenetrating (3, 6)-connected net with (611·84) (63)2 topology. The complex 5 shows a (3, 8)-connected network with a point symbol of (4·62)2 (42·615·78·8·92) topology. The complex 6 exists a 2-fold interpenetrating topology framework and the point symbol is (6·6·6). Moreover, the photocatalytic studies show that complexes 1-5 have highly photocatalytic ability to degrade methylene blue (MB). In addition, the complex 6 can efficiently adsorb Congo red through H-bonds and the adsorption kinetic have been discussed.